Driving Mechanism for Manufacturer’s Decision of Green Innovation: From the Perspectives of Manager Cognition and Behavior Selection - Han, Minghua; Zheng, Daliang; Gu, Danyi (Frontiers in Psychology, 2022)
From the perspectives of manager cognition and behavior selection, this paper analyzes the cognitive basis of manufacturer green innovation, and discovers that the embodied cognition of the manager has an important influence on the selection of green innovation behavior. Next, the behavior activation in the four stages of manufacturer green innovation, namely, initiation, termination, change, and solidification, were analyzed, and two behavior selections were proposed: the adaptive legitimacy with institutional logic as the cognitive starting point, and the strategic legitimacy with efficiency logic as the cognitive starting point. On this basis, the authors examined four types of manufacturer decisions of green innovation (compliance, selection, creation, and control) driven by manager cognition and behavior selection. The examination reveals how should the manager, facing the growing environmental pressure, form a correct cognition and select the right behavior, and make the proper green innovation decision, which promotes the green, sustainable development of manufacturers.